Aliran Filsafat Pendidikan Progresivisme Dalam Pendidikan Islam - Muhammad Irsyad Salsabila; M.Syarifur Rijal Wahyullah; M Yunus Abu Bakar (JOURNAL SAINS STUDENT RESEARCH, 2024)
Islamic education is the process of developing students' potential through teaching, habituation, guidance, nurturing and supervision to obtain various knowledge and Islamic values to realize the perfection of life both in this world and the hereafter. Philosophizing for some people is a hard job. Philosophizing is thinking, reflecting, contemplating, analyzing, reflecting and even thinking evaluatively. According to language, the term progressivism comes from the word progressive, which means moving forward. In the Big Indonesian Dictionary it is stated that the word progressive is defined as moving towards progress; aiming for improvement now; and rising levels. Education is a cultural process, therefore it grows and develops in the cultural flow of each society and often originates from the religion and traditions adhered to by the community so that its presence has strong roots in the culture of the community. Progressive education encourages a flexible learning approach and respects individual differences. Because each student has unique potential, rigid and authoritarian learning methods are not in accordance with the principles of progressivism.